2021
DOI: 10.4018/ijcrmm.2021010101
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Ethical and Other SMEs Internationalisation Determinants and Its Impact on Business Performance

Abstract: The research in hand attempts to investigate the different factors influencing SMEs' decision to internationalise in developing countries (such as Malaysia) including the impacts of ethical issues on the internationalisation decision process. The study also attempts to investigate the impact of internationalisation adoption on SMEs' business performance since the relationship remains vague. The study will deepen the understanding of the complex interrelationship between internationalisation determinants (that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 113 publications
(150 reference statements)
0
6
0
Order By: Relevance
“…Second, SMEs working in the knowledgeintensive sector were considered. The selection of knowledge-intensive SMEs was guided by previous empirical research in the area (Gyarteng-Mensah et al 2021;Zaki et. al., 2021;Hamad et al, 2018Hamad et al, , 2015Dosumu et al, 2017;El-Gohary, 2012;Giauque et al, 2010;Khalique et al, 2018;Ojala, 2009;Yusoff et al, 2016;Ramezan, 2012;Jeong et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Second, SMEs working in the knowledgeintensive sector were considered. The selection of knowledge-intensive SMEs was guided by previous empirical research in the area (Gyarteng-Mensah et al 2021;Zaki et. al., 2021;Hamad et al, 2018Hamad et al, , 2015Dosumu et al, 2017;El-Gohary, 2012;Giauque et al, 2010;Khalique et al, 2018;Ojala, 2009;Yusoff et al, 2016;Ramezan, 2012;Jeong et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have shown that SMEs that apply financial knowledge to a higher level of entrepreneurial activity have the opportunity to be more successful in running their businesses. Financial literacy guides business actors to make sound financial decisions and use the increasingly complex choices of financial products offered by the financial system in a fair manner (Candiya Bongomin, 2017; Zaki et al, 2021).…”
Section: The Effect Of Financial Literacy On Business Performancementioning
confidence: 99%
“…Considering that the unit of ana lysis is SME, then the respondent in this study was the owner/manager. Each SME was represen ted by one person responsible for the management of the SME in the last year (Zaki et al, 2021).…”
Section: Samplementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the published work within the field highlighted the importance of SME contributions to economic growth, innovation, poverty relief, and employment growth worldwide. The works of Rayappa and Arora ( 2021 ), Weqar et al ( 2021 ), Wu and Wu ( 2020 ), Sirgy ( 2019 ), Dosumu et al ( 2017 ), Zaki et al ( 2021 ), Du et al ( 2015 ), Ramaswamy ( 2014 ), Cernat and Gourdon ( 2012 ), Beck et al ( 2011 ), Kalhoro et al ( 2011 ), Storey and Greene ( 2010 ), European Union ( 2009 ), Storey ( 1994 ), Hamad et al ( 2018 ), and Shah et al ( 2015 ) are just few examples of such published work. However, by looking at the literature, it is noticed that most of the literature focused on other industries and not on tourism (Jaafar et al, 2011 ), whereas it managed to gain attention as an effective tool to initiate progress in developed countries (UK, USA, etc.)…”
Section: Introductionmentioning
confidence: 99%